2002
DOI: 10.1136/jnnp.73.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bed rest after mild traumatic brain injury: a randomised trial of no versus six days of bed rest

Abstract: Background: Outcome after mild traumatic brain injury (MTBI) is determined largely by the appearance of post-traumatic complaints (PTC). The prevalence of PTC after six months is estimated to be between 20 and 80%. Bed rest has been advocated to prevent PTC but its effectiveness has never been established. Objective: To evaluate the effect of bed rest on the severity of PTC after MTBI. Methods: Patients presenting with MTBI to the emergency room were randomly assigned to two intervention strategies. One group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 24 publications
1
92
1
Order By: Relevance
“…This reinforces that extended bedrest after MTBI does not result in better recovery than return to usual activities (de Kruijk et al, 2002). …”
Section: Treatmentssupporting
confidence: 58%
See 1 more Smart Citation
“…This reinforces that extended bedrest after MTBI does not result in better recovery than return to usual activities (de Kruijk et al, 2002). …”
Section: Treatmentssupporting
confidence: 58%
“…The second study was a Dutch study (de Kruijk et al, 2002), comparing the effectiveness of extended bedrest to promote a return to activities. The intervention group were assigned to 6 days of full bedrest and told to return to full activity between 7 and 11 days; the control group was encouraged to remain on bed rest for no more than 4 hours during the first day then told to return to full activity within 4-days post injury.…”
Section: Treatmentsmentioning
confidence: 99%
“…37 de Kruijk et al (2002) randomized adults discharged with acute mTBI to usual care or strict bedrest and found that both treatments resulted in no significant differences in actual amounts of outpatient bedrest and no differences in outcomes at 2 weeks, 3 months, and 6 months. 38 Given that these previous studies of more stringent rest in concussed adults similarly failed to demonstrate…”
Section: Discussionmentioning
confidence: 96%
“…Mild (or 'minor') head injury should have a GCS score of R13. Such an injury will have been caused by a blunt blow to the head in which post-traumatic amnesia lasts for !1 h. If there was an initial loss of consciousness at the time of injury, then it would have been !15 min duration and there is an absence of focal neurological signs (15). Children with a GCS %8 have severe head injury.…”
Section: Epidemiology Of Tbi In Children and Adolescentsmentioning
confidence: 99%